A pilot study on cytochrome p450 2B6 single nucleotide polymorphism among Fulani ethnic group of Northwest Nigeria. - Umar, M.T.*1, Abubakar, M.B. 2, Chika, A. 1, Gada, Y.A. 1 (Sokoto Journal of Medical Laboratory Science)
Cytochrome 2B6 is one of the most polymorphic human cytochromes that metabolizes a wide range of clinically important drugs used as antimalarial, anti-retroviral, anesthetics, statins and anti-cancer. About 40-70% of patients demonstrate a lack of efficacy of drug response or adverse drugs reactions due to high intra and inter-individual variability and the greater majority of this variability is accounted for by genetic polymorphism of genes encoding the drugs metabolizing cytochrome p450 enzymes. Fulani constitutes a major ethnic group not only in Nigeria but the whole of West Africa where malaria is endemic and poses major health challenge. Participants were drawn from Wamakko and Dange- Shuni Local Government Areas of Sokoto State. Five milliliters of whole blood from each participant were collected for DNA extractions. PCR and Gel electrophoresis were carried out at Centre for Advanced Medical Research and Training, Usmanu Danfodiyo University, Sokoto using the QIAamp DNA blood mini kit using manufacturer's instructions. All the participants were Muslims, with mean age of 24.6±1.1 and mean body weight of 59.1±1.9 Kg. Fifty percent were intermediate metabolizers, 33.3 and 16.7% were extensive and poor metabolizers respectively. A good percentage of the participants were poor metabolizers. More elaborate studies involving large sample sizes are recommended.